Literasi Keuangan Digital Bagi Generasi Muda di Pimpinan Daerah ‘Aisyiyah (PDA) Karanganyar - civi erika; Ayuk Setiyawan; Nur Amalina; Adik Aditya; Lutfiyah Mumtaz (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
This community service aims to provide education and training on the importance of digital financial literacy to the younger generation under the auspices of the Regional Leadership of ‘Aisyiyah (PDA) Karanganyar.The target participants of this program are members of the Aisyiyah School of Entrepreneurship (SWA), consisting of orphaned youth living in the Aisyiyah Girls’ Orphanage dormitory. The challenge faced by PDA Karanganyar itself is the lack of financial literacy education and entrepreneurship training. Therefore, we provide a solution by carrying out community service through education and training for the young generation of SWA. Digital financial literacy is very important to apply in daily life. Advancing technology requires us to adapt to current situations and conditions. With digital financial literacy education for young people, it is expected that they will be able to manage finances wisely, make use of facilities to simplify tasks, avoid impulsive spending, and prevent negative impacts of digital finance such as online loans (pinjol). The method used in this community service is lectures, delivering material related to the benefits and importance of digital financial literacy education for the younger generation. The results of the community service show that participants understood the material presented, as evidenced by their enthusiasm in asking questions and actively participating in discussions. It is hoped that from the results of this community service, participants will be able to apply digital financial literacy in their daily lives and inspire other young people to understand the importance of digital literacy and have the courage to start entrepreneurship. The plan for the next community service program is to provide training on how to maximize promotion through social media, start a business, and utilize affiliate marketing on their social media platforms.